Improving the Grinding Performance through Modelling and Simulation: The Case of Buzwagi Gold Mine (BGM) - A. Wikedzi; U. A. Peuker; T. Mütze; F. Shayo (International Mineral Processing Congress, 2018)
"Buzwagi Gold Mine (BGM) is operated by Acacia Mining and located in the Lake Victoria Goldfields of central Tanzania. The mine treats a sulphide copper-gold ore to produce gold in form of doré bars and a concentrate containing gold, copper and silver. The BGM comminution circuit includes a primary crushing stage with a gyratory crusher and two grinding circuits using a Semi-Autogenous Grinding (SAG) mill and a ball mill. Currently, the grinding circuits are inefficient in achieving the aspired product fineness of xP,80 = 125 µm even at low to normal throughputs (450-600 t/h). An optimization study of the circuit performance was conducted to improve product fineness through circuit surveys, experimental lab work and simulations. The analysis of survey data revealed inefficient grinding operation characterized by ball mill product (xP,80 > 400 µm) coarser than designed and higher hydrocyclone cut sizes (xT > 200 µm), too. In MODSIM several options were simulated such as reduction of vortex finder and apex diameters, reduction of SAG screen aperture, and modification of cyclone feed density. An improvement of product fineness could be achieved by simulation of the cumulative changes but it was also concluded that the current equipment cannot achieve the target. Further simulations showed that a second ball mill might help to achieve the desired fineness as well as an increase of grinding throughput by up to 26 %. INTRODUCTION Simulation of comminution, particularly grinding and classification, has received great attention for many years, due to the fact that the unit operation is by far the most important both in terms of energy consumption as well as overall plant performance (King, 2001; Wills et al., 2006). The use of simulation is advantageous due to low cost as well as its ability to consider many variables simultaneously. Moreover, there are some benefits for optimizing grinding operations by simulation like decreased unit operating costs, increased capacity, and improved performance of downstream processes due to improved feed size distribution. This paper presents an optimization study for the grinding efficiency at Buzwagi Gold Mine. This was achieved through three full scale circuit surveys, lab work and simulations with MODSIM."